Radical cystectomy in patients with disseminated disease: An assessment of perioperative outcomes using the National Surgical Quality Improvement Program database - Wallis, Christopher; Khana, Suneil; Hajiha, Mohammad; Nam, Robert K.; Satkunasivam, Raj (Canadian Urological Association Journal, 2017)
Introduction: We sought to determine the effect of the presence of disseminated disease on perioperative outcomes following radical cystectomy for bladder cancer. Methods: We identified 4108 eligible patients who underwent radical cystectomy for bladder cancer using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database. We matched patients with disseminated cancer at the time of surgery to those without disseminated cancer using propensity scores. The primary outcome of interest was major complications (death, reoperation, cardiac or neurological event). Secondary outcomes included pulmonary, infectious thromboembolic, and bleeding complications, in addition to prolonged length of stay. Generalized estimating equations were used to examine the association between disseminated cancer and the development of complications. Results: Following propensity score matching and adjusting for the type of urinary diversion, radical cystectomy in patients with disseminated disease was associated with a significant increase in major complications (8.6% vs. 4.0%; odds ratio [OR] 2.50; 95% confidence interval [CI] 1.02–6.11; p=0.045). The presence of disseminated disease was associated with an increase in pulmonary complications (5.8% vs. 1.2%; OR 5.17. 95% CI 1.00‒26.66. p=0.049), but not infectious complications, venous thromboembolism, bleeding requiring transfusion, and prolonged length of stay (p values 0.07–0.79). Conclusions: Patients with disseminated cancer undergoing cystectomy are more likely to experience major and pulmonary complications. The strength of these conclusions is limited by sample size, selection bias inherent in observational